Radio Frequency and Microwave Heating of Preceramic Polymer Nanocomposites with Applications in Mold‐Free Processing. Issue 8 (4th June 2019) - Patil, Nutan; Camacho, Alejandro Cardenas; Mishra, Naveen K.; Singhla, Prashant; Sweeney, Charles B.; Saed, Mohammed A.; Radovic, Miladin; Green, Micah J.
Abstract : Here the authors demonstrate an oven‐free and mold‐free heating route to convert preceramic polymers to silicon carbide using carbon nanomaterials as susceptors. Silicon carbide is prized for its high thermal stability and low density and could be produced via slow oven heating of polycarbosilane (PCS). The authors show that addition of multiwalled carbon nanotubes (MWCNT) as susceptors to polycarbosilane results in rapid and volumetric heating upon exposure to microwaves and radio frequency. The authors assess microwave heating of polycarbosilane‐MWCNT composites; this process is capable of reaching pyrolysis temperatures, and the resulting crystal structure is cubic (β‐SiC). Dielectric properties of these composites in the radio frequency range is measured. The authors cure these composites using RF, and thermogravimetric data shows that the extent of cure for these samples is around 95%. The applicability of this study for 3D printing silicon carbides by successive iterations of layer deposition and rapid RF curing is demonstrated. The fly measurements of dielectric values of the 3D printing ink at different temperature while curing it is performed. The authors have also shown that these volumetric heating methods can rapidly cure polycarbosilane fibers to make silicon carbide fibers without melting them before crosslinking. Abstract : In this paper, microwaves (2.45 GHz) and radio frequencies (1–200 MHz) are coupled with multiwalled carbon nanotube‐polycarbosilane (preceramic polymer) composites to form silicon carbide. Dielectric properties of these composites are studied in 50–500 MHz range at different temperatures as they cure. This heating method is applied for rapid curing in 3D printing and fiber processing application.